2013
DOI: 10.2169/internalmedicine.52.9416
|View full text |Cite
|
Sign up to set email alerts
|

Tracheobronchial Involvement in Relapsing Polychondritis Diagnosed on Endobronchial Ultrasound

Abstract: Respiratory tract chondritis is not uncommon in patients with relapsing polychondritis (RP); however, diagnosing this condition remains problematic, especially in patients whose extrapulmonary manifestations do not predominate, as there are broad differential diagnoses of airway obstruction. We herein report the case of a 56-year-old man who presented with cough and dyspnea. Computed tomography of the chest demonstrated diffuse smooth thickening of the visualized tracheobronchial wall with a moderately narrowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 9 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…Although some previous studies reported the clinical implications of imaging tests such as contrast‐enhanced CT, MRI, FDG‐PET/CT and bone scintigraphy for assessment of disease activity, 9–16 performing these imaging tests frequently is unrealistic without careful consideration of cost, convenience, invasiveness and radiation exposure. In tracheal chondritis—one of the fatal complications in RP—it has been reported that endobronchial ultrasonography is useful for monitoring disease activity 30–32 . Swelling of the submucosal and cartilage layer and improvement in swelling is observed when the disease activity is high and low, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some previous studies reported the clinical implications of imaging tests such as contrast‐enhanced CT, MRI, FDG‐PET/CT and bone scintigraphy for assessment of disease activity, 9–16 performing these imaging tests frequently is unrealistic without careful consideration of cost, convenience, invasiveness and radiation exposure. In tracheal chondritis—one of the fatal complications in RP—it has been reported that endobronchial ultrasonography is useful for monitoring disease activity 30–32 . Swelling of the submucosal and cartilage layer and improvement in swelling is observed when the disease activity is high and low, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In tracheal chondritis—one of the fatal complications in RP—it has been reported that endobronchial ultrasonography is useful for monitoring disease activity. 30 , 31 , 32 Swelling of the submucosal and cartilage layer and improvement in swelling is observed when the disease activity is high and low, respectively. In contrast, because bronchoscopy itself is highly invasive and may cause respiratory failure, it is critical for clinicians to be careful about its indication.…”
Section: Discussionmentioning
confidence: 99%